Hubungan Akses Informasi Kesehatan dengan Pengetahuan Kesehatan Reproduksi pada Mahasiswa Universitas Islam Negeri Syarif Hidayatullah Jakarta - Anggi Fitria; Jihan Safitri; Hoirun Nisa (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Sexually transmitted infections (STIs) among young adults continue to be an important public health problem for many countries, with as many as 333 million cases of STIs occurring among young adults. The lack of reproductive health information driven by socio-cultural changes for young adults makes students vulnerable to reproductive diseases. Information obtained through the media is needed which aims to increase student or young adult knowledge regarding reproductive health. This study aims to see the relationship between access to reproductive health information and students' knowledge related to reproductive health. This study used a quantitative method with a cross sectional approach. The population of this study is all active students at UIN Syarif Hidayatullah Jakarta in 2022, that involved a sample of 266 students using a proportionate stratified random sampling . Data were analyzed using the chi-square test for categorical variables and t-test for continuous variables. A total of 83.5% of students access reproductive health information. Data analysis shows that there is a relationship between information access to knowledge of reproductive health, from the results of the chi square statistical test found p-value < 0.001. Meanwhile, there was no relationship between age, gender, and faculty with knowledge of reproductive health.